Carte générale de l'Amérique du Nord et des Iles qui en dépendent. - Dufour, A.-H. (Auguste-Henri), 1798-1865 (1851)
Map shows major cities and areas of Native American habitation in North America, Central America, and the West Indies; western territories of the United States, Russian America [Alaska], pre-Gadsden Treaty boundary between Mexico and the United States; state and territorial boundaries. Relief shown by hachures. Scale [ca. 1:26,610,000].